1995
DOI: 10.1017/s0025315400015174
|View full text |Cite
|
Sign up to set email alerts
|

Movement Patterns and Migrations in Crabs: Telemetry of Juvenile and Adult Behaviour in Callinectes Sapidus and Maja Squinado

Abstract: Late stage juveniles and adults of Callinectes sapidus in Chesapeake Bay, USA, and Maja squinado off the Ria de Arousa, Spain, were compared for ontogenetic changes in movement patterns (speed, distance, orientation) and habitat selection (depth, substrate) using ultrasonic telemetry and published information. After settling in submerged grass beds in the lower Bay, 20-mm juvenile C. sapidus disperse long distances into low salinity sub-estuaries to feed and grow to maturity in two years. Within the Rhode Rive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 32 publications
(39 reference statements)
2
68
0
1
Order By: Relevance
“…Many of these broad-scale physical hydrodynamics are cyclical and animals have evolved behavioural interactions such as the scheduling of spawning to coincide with lunar phases, seasonal winds and tidal currents (Norcross and Shaw, 1984;Morgan and Christy, 1994;Botsford et al, 2001), or to place the juvenile 'growing season' in the warmer, more productive months of the year (Conover, 1992). For example, in Chesapeake Bay, USA, hatching of blue crab larvae (Callinectes sapidus) mainly coincides with night-time ebb tides, which distribute progeny offshore in spring and summer when planktonic food resources for larvae are most abundant (Hines et al, 1995). Clearly, this spatio-temporal scheduling of life histories is critical to the maintenance of populations.…”
Section: Movements Of Eggs and Larvaementioning
confidence: 99%
See 3 more Smart Citations
“…Many of these broad-scale physical hydrodynamics are cyclical and animals have evolved behavioural interactions such as the scheduling of spawning to coincide with lunar phases, seasonal winds and tidal currents (Norcross and Shaw, 1984;Morgan and Christy, 1994;Botsford et al, 2001), or to place the juvenile 'growing season' in the warmer, more productive months of the year (Conover, 1992). For example, in Chesapeake Bay, USA, hatching of blue crab larvae (Callinectes sapidus) mainly coincides with night-time ebb tides, which distribute progeny offshore in spring and summer when planktonic food resources for larvae are most abundant (Hines et al, 1995). Clearly, this spatio-temporal scheduling of life histories is critical to the maintenance of populations.…”
Section: Movements Of Eggs and Larvaementioning
confidence: 99%
“…However, some direct evidence has been provided through telemetric and tagging studies. For example, using ultrasonic telemetry, Hines et al (1995) showed an ontogenetic change in movement pattern of juvenile blue crabs (Callinectes sapidus) in Chesapeake Bay. After settlement to seagrasses, the crabs moved between 50-250 km into shallower, brackish water sub-estuaries in order to evade predators, feed and grow.…”
Section: Ontogenetic Shiftsmentioning
confidence: 99%
See 2 more Smart Citations
“…Los juveniles de Maja sp. habitan aguas poco profundas, de no más de 15 metros de profundidad, con sustratos arenosos y/o rocosos (Hines et al 1995). La madurez sexual se produce tras la denominada muda terminal, que tiene lugar durante el verano en juveniles de unos dos años de edad .…”
Section: Introductionunclassified